If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4) = 9x + -33 Reorder the terms: (-4 + x) = 9x + -33 Remove parenthesis around (-4 + x) -4 + x = 9x + -33 Reorder the terms: -4 + x = -33 + 9x Solving -4 + x = -33 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -4 + x + -9x = -33 + 9x + -9x Combine like terms: x + -9x = -8x -4 + -8x = -33 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 + -8x = -33 + 0 -4 + -8x = -33 Add '4' to each side of the equation. -4 + 4 + -8x = -33 + 4 Combine like terms: -4 + 4 = 0 0 + -8x = -33 + 4 -8x = -33 + 4 Combine like terms: -33 + 4 = -29 -8x = -29 Divide each side by '-8'. x = 3.625 Simplifying x = 3.625
| 64x^2+34x+1=0 | | 5x-1=2+15 | | -2r+4=(-3)+9 | | x-2.5= | | f(t)=-3t^2+24t-36 | | 24+18x=90 | | 5x+2=3+32 | | -9=-3-n | | t^434343-t^434342=0 | | 5x-2=7x-4 | | 10-x=4x+3 | | -1=5x+6/6 | | 5x+135=0 | | 13+6x=3+11x | | 47+0.41666666666x=100 | | (64x^2-1)=0 | | -2x+4=-4x+12 | | 0=3x^2-6x-9 | | 4+7x=5x-18 | | 13x-74=78 | | 2x+4+2x-6=6x+20 | | 3x=36-5 | | 133-(-267)= | | 0=3(x^2-2x-9) | | 45x+30y+105= | | 652-425= | | -14+22=m-5 | | 2x-4=-5+10 | | 6f+6=0 | | -11n+5=-10n-12 | | -3-14= | | x+7-2=5 |